Game performance analysis of soccer goalkeepers comparison between saving motion and other motions - Numazu, N.; Fujii, N.; Nakayam, M.; Koido, M. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purposes of this study were to clarify the most important goalkeeper (GK) motion of the various motions, such as saving motion and other motions to evaluate the performance and to analyze the most important motion biomechanically. Data were obtained from 27 official games from 2014 Kanto University League and others. The novel findings in this study are summarized as follows: (1) the corresponding motion to the shot was the important motion in the performance of goalkeepers in comparison with other performances.(2) it is assumed that the saving motion with the preparatory motion should be analyzed preferentially for improvement of GK motion, (3) corresponding motion to the centering and throwing are the second and third most important motions for the GK next to the corresponding motion to the shot during a game.